Steinernema weiseri n. sp. (Rhabditida, Steinernematidae), a new entomopathogenic nematode from Europe - Mrácek, Z; Sturhan, D; Reid, A (Systematic parasitology, 2003)
Steinernema weiseri n. sp. is described from a roadside with apple trees near Ceské Budejovice, Czech Republic. The species is also widely distributed in Germany and Slovakia, from where it had previously been reported as Steinernema spec. F. The British Steinernema sp. D1 is considered conspecific with S. weiseri n. sp. Males of the new species are mainly characterised by light brown, slightly curved spicules with a long manubrium and the presence of a short tail mucron in the second generation. Third-stage infective juveniles are characterised by a 'medium size' body and tail length, short hyaline tail portion (mostly around 1/3 of tail length), the excretory pore situated in the mid-pharynx region, lip region slightly offset, angular and flattened, and the lateral field having nine equally developed lines separated by eight distinct ridges. S. weiseri n. sp. is most similar to S. feltiae, with which it did not hybridise. RFLP analysis of the ITS region of the rDNA repeat shows S. weiseri n. sp. to be distinct from 50 other Steinernema species and isolates. The new species was found in a wide range of habitats and is readily maintained on Galleria mellonella larvae.
Keywords: Rhabditida; Insecta; DNA helmintů; DNA, Helminth; polymerázová řetězová reakce; Male; Česká republika; ribozomální DNA; mužské pohlaví; mezerníky ribozomální DNA; Soil; Czech Republic; Animals; ženské pohlaví; Microscopy, Electron, Scanning; hmyz; zvířata; polymorfismus délky restrikčních fragmentů; DNA, Ribosomal Spacer; Polymerase Chain Reaction; DNA, Ribosomal; půda; Female; mikroskopie elektronová rastrovací; Polymorphism, Restriction Fragment Length